The romance of a romantic country: landscapes and historical-artistic memories in Anne MacDonell's and Amy Atkinson’s Abruzzi (Altre Modernità, 2023)
In the Spring of 1907 the British writer Anne MacDonell and the English painter Amy Atkinson had a journey through the Abruzzi. Their travel account, illustrated by watercolours, was published in the book In the Abruzzi (London, 1908). The descriptions of the landscapes, suitable settings for literary works created during the Romantic era, and the digressions on the monuments in this region, interspersed with quotations from D’Annunzio’s works, are a privileged observatory to understand the features of a written work that was reviewed by contemporaries as a “romance of a romantic country”.
Keywords: Abruzzo; travel book; landscape; landmark